Calculations of two new dose metrics proposed by AAPM Task Group 111 using the measurements with standard CT dosimetry phantoms. Issue 8 (18th July 2013) - Li, Xinhua; Zhang, Da; Liu, Bob
Abstract : Purpose: : AAPM Task Group 111 proposed to measure the equilibrium dose‐pitch product D ̂ eq for scan modes involving table translation and the midpoint dose D L (0) for stationary‐table modes on the central and peripheral axes of sufficiently long (e.g., at least 40 cm) phantoms. This paper presents an alternative approach to calculate both metrics using the measurements of scanning the standard computed tomographic (CT) dosimetry phantoms on CT scanners. Methods: : D ̂ eq was calculated from CTDI100 and ε(CTDI100 ) (CTDI100 efficiency), and D L (0) was calculated from D ̂ eq and the approach to equilibrium function H ( L ) = D L (0)/ D eq, where D eq was the equilibrium dose. CTDI100 may be directly obtained from several sources (such as medical physicist's CT scanner performance evaluation or the IMPACT CT patient dosimetry calculator), or be derived from CTDIVol using the central to peripheral CTDI100 ratio ( R 100 ). The authors have provided the required ε(CTDI100 ) and H ( L ) data in two previous papers [X. Li, D. Zhang, and B. Liu, Med. Phys. 39, – (2012)10.1118/1.3678990 ; X. Li, D. Zhang, and B. Liu, Med. Phys., 031903 (10pp.) (2013)10.1118/1.4790470 ]. R 100 was assessed for a series of GE, Siemens, Philips, and Toshiba CT scanners with multiple settings of scan field of view, tube voltage, and bowtie filter. Results: : The calculated D L (0) and D L (0)/ D eq in PMMA and water cylinders were consistent with the measurements on two GE CT scanners (LightSpeed 16 and VCT) by Dixon and Ballard [Med. Phys. 34, 3399–3413 (2007)10.1118/1.2757084 ], the measurements on a Siemens CT scanner (SOMATOM Spirit Power) by Descamps et al. [J. Appl. Clin. Med. Phys. 13, 293–302 (2012)10.1120/jacmp.v13i6.3934 ], and the Monte Carlo simulations by Boone [Med. Phys. 36, 4547–4554 (2009)10.1118/1.3223634 ]. Conclusions: : D ̂ eq and D L (0) can be calculated using the alternative approach. The authors have provided the required ε(CTDI100 ) and H ( L ) data in two previous papers. R 100 is presented for a majority of multidetector CT scanners currently on the market, and can be easily assessed for other CT scanners or operating conditions not covered in this study. The central to peripheral D eq ratio is about 1.50 and 1.12 times of R 100 for the 32‐ and 16‐cm diameter PMMA phantom, respectively.